Learning and behavior - Mazur, James E. (Upper Saddle River, N.J. : Prentice Hall, 2006)
This book examines how people and animals learn and how their behaviors are later changed. This text is designed for introductory or intermediate level courses in learning, conditioning, or the experimental analyses of behavior. Chapter 1 discusses the nature of scientific theories and experiments, and contrasts the behavioral and cognitive learning approaches. Chapter 2 describes theories about the learning process. Chapters 3 and 4 discuss innate behaviors and habituation and examine basic principles of classical conditioning. Chapter 5 describes more recent theoretical developments and experimental findings in this area. Chapters 6,7, and 8 involve operant conditioning and examine positive reinforcement; schedules of reinforcement; and negative reinforcement and punishment, respectively. Chapter 9 presents differing views on such questions as what constitutes a reinforcer and what conditions are necessary for learning to occur. Chapter 10 takes a more thorough look at generalization and discrimination and examines research on concept formation. Chapter 11 surveys a wide range of findings in the area of comparative cognition. Chapters 12 and 13 discuss observational and motor-skills learning. Finally, Chapter 14 presents an overview of behavioral research on choice.
Choice
Keywords: učenje; ponašanje